2007
DOI: 10.3122/jabfm.2007.01.060026
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Depression in Primary Care: Missed Opportunities for Diagnosis and Education

Abstract: Purpose: Depression is one of the most commonly encountered chronic conditions in primary care, yet it remains substantially underdiagnosed and undertreated. We sought to gain a better understanding of barriers to diagnosis of and entering treatment for depression in primary care.Methods: We conducted and analyzed interviews with 15 subjects currently being treated for depression recruited from primary care clinics in an academic medical center and an academic public hospital. We asked about experiences with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 28 publications
1
34
0
2
Order By: Relevance
“…[51][52][53][54] Encouraging patients to discuss their Internet findings with their doctors would be a way of improving this situation; however, doctors often feel that the patient who brings information retrieved from the web to discuss is challenging their authority, and that they make the visit less time-efficient. 55 If consumers have difficulties appraising and discussing the information they find on the web with their doctors, they may end up making uncritical healthcare decisions based on non-evidence-based information.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54] Encouraging patients to discuss their Internet findings with their doctors would be a way of improving this situation; however, doctors often feel that the patient who brings information retrieved from the web to discuss is challenging their authority, and that they make the visit less time-efficient. 55 If consumers have difficulties appraising and discussing the information they find on the web with their doctors, they may end up making uncritical healthcare decisions based on non-evidence-based information.…”
Section: Discussionmentioning
confidence: 99%
“…2 Despite this prevalence, very few cohort studies have examined the incidence of depressive disorders in this setting. Some have assessed incidence using physicians' case reports or retrospective reviews of medical records for case identification 3,4 ; however, systematic reviews have shown that roughly 50% of depressive disorders are missed in primary care 5 ; hence, such estimates may exclude patients who have not been identified as having depression by a physician. One way to overcome this issue is by using patient self-reported symptoms for case finding.…”
Section: Introductionmentioning
confidence: 99%
“…4 Suboptimal levels of recognition and treatment are due to a variety of physician, health system, and patient factors. [4][5][6][7] The present study is part of the formative research of a larger project that will develop and evaluate offi ce-based interventions to encourage seeking care for depression. This research is grounded in a model that assumes self-disclosure of depression is a key step on the road to appropriate diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%